(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2020)
At his death in 1945, Sir James William Barrett, a medical doctor in the state of Victoria, left a bequest to the University of Melbourne, his alma mater. Barrett’s entire professional life was conducted at the University. According to his will, Barrett had been so influenced by his experiences of American universities which offered education in nursing that he directed a sum of money to the University of Melbourne for the foundation and/or development of a school of nursing. The background to Barrett’s bequest is a complex episode in Australian nursing education history that has received little attention. In the 1920s and early 1930s, Barrett was a central actor in plans to develop a diploma of nursing to be conducted at the University of Melbourne. After 10 years of sometimes vitriolic debate over the idea, defeat was snatched from the jaws of victory as support for the scheme fractured. This paper addresses the circumstances of the failed diploma program in Victoria. I account for its genesis, its rise, ultimate fall, and its legacy by examining the context for Barrett’s promotion of university-based education, identifying advocates and opponents of the diploma scheme, and assessing their respective motivations. Primary sources accessed include: records of nursing professional organizations in Australia and elsewhere, university and other institutional archives in Australia and the United States of America, newspapers, and papers of private individuals. A fresh analysis of this period demonstrates how Australian models compared with international schemes in the 1920s and 1930s, and reflects the challenges in developing nursing education. It underscores fundamental tensions over the essence of education in Australian nursing and highlights issues that remain perennial and helps to understand why the transfer of pre-registration nursing and midwifery in Australia from apprenticeship models to the higher education sector was so contested.